Ethnobotany of three sea grass species from Port Blair, a step towards its conservation in Andaman Islands - PJ, Mohammed Naufal; Padmavati, G (Journal of Tropical Life Science, 2021)
Ethno-phycology is the study of the relationships of human society to flora and its ecosystem. In the marine world, ethno-biology is a thriving area of research which have yielded valuable ethno-biological knowledge. The main goal of the present study was to understand the effect of abiotic factors as well as the natural and anthropogenic disturbances that shape seagrass community in Andaman Island and to reveal the knowledge of the local people, about the significance of seagrass habitat and its conservation. The qualitative study on distribution of seagrasses in Chidiyatapu (11° 29' 30